ANALISIS TINGKAT KESEJAHTERAAN PENGEMUDI MAXIM DI KOTA BANDAR LAMPUNG PERSPEKTIF MAQASHID SYARIAH - Irfan Aditia; Abizar; Ruslaini; Ulil Albab (JOURNAL ISLAMIC ECONOMICS AD DIWAN, 2026)
This research aims to analyze the welfare level of Maxim drivers in Bandar Lampung City based on five dimensions of maqashid syariah: the preservation of religion (din), life (nafs), intellect ('aql), lineage (nasl), and wealth (mal). The research method employed is qualitative with a phenomenological approach. Data were obtained through in-depth interviews with 30 Maxim driver informants selected purposively. The research findings indicate that the profession as an online motorcycle taxi driver for Maxim has not yet comprehensively fulfilled the principles of maqashid syariah. The main obstacles were found in the aspect of life preservation (hifz al-nafs) regarding physical fatigue and psychological pressure, and wealth preservation (hifz al-mal) with the reality of fluctuating income that results in unmet basic needs. Nevertheless, forms of adaptation and differences in perception in facing existing challenges were also discovered. This research recommends policy interventions from companies and government to support overall driver welfare based on Islamic values